URGENSI PENEGAKAN ASAS MONOGAMI DAN PENYETARAAN GENDER DALAM HUKUM PERKAWINAN INDONESIA - Aulia, Farah Nizrina; Rato, Dominikus; Ali, Mohammad (Prodi Ilmu Hukum, Universitas Teuku Umar, 2025)
The principle of monogamy as stated in the Indonesian Marriage Law is the principle adopted by the law, which states that in a marriage a husband may only have one wife and vice versa. However, the law also explains the permissibility of a husband practicing polygamy or having more than one wife by fulfilling the stipulated requirements. Often in practice, the right to polygamy is misused so that injustice or gender inequality arises. In addition, the Compilation of Islamic Law (KHI) is also the basis for regulating polygamy, which is regulated in Articles 55 to 59. Article 55 of the KHI firmly states that a man who practices polygamy will be limited to up to four wives by fulfilling the main requirement, namely that there must be fair treatment from the husband towards his wife and children. If the husband violates the main requirements, then he is not allowed to practice polygamy. The researcher uses a normative legal method in research or is generally called doctrinal legal research, this method is a method that emphasizes the investigation of the application of legal norms or positive rules that are enforced and associated with the enforcement of the principle of monogamy in Indonesian marriage law. In addition, this study uses a comparative technique between marriage law and a compilation of Islamic law related to the principle of monogamy that is enforced in marriage in Indonesia. Polygamy in marriage in Indonesia must be understood as an alternative path or a choice to do it or not in a truly emergency situation. Therefore, the principle of monogamy needs to be enforced, namely by a man being limited to having more than one wife except in urgent conditions.